Perancangan Website sebagai Media Pemasaran Digital UMKM Tuku Jajanan Padang - Tari Nurlaini; Chelsi Aprilia Hidayat; Gita Aulia Rahman; Zulfitri Yani; Sularno Sularno (CV. ITTC INDONESIA, 2026)
Limited market reach remains a structural obstacle that frequently constrains the competitiveness of micro, small, and medium enterprises (MSMEs) in the digital era. This Project Based Learning (PBL) activity aims to examine the digital marketing needs of the culinary MSME Tuku Jajanan Padang and to design a website that serves as a representative digital marketing medium. The methods applied include field observation, an in-depth interview with the business owner, identification of system requirements, interface design on the SITE123 platform, and evaluation of the design outcomes. The findings show that this MSME possesses strong product potential but has so far depended entirely on a single Instagram account, without a more structured digital channel. The resulting website integrates eight main components-a homepage, brand narrative, profile video, beverage and food catalogs, service standards, and an integrated location map-and is accessible at http://6a2bf9ed7b5ed.site123.me. This website is expected to broaden market reach, strengthen business credibility, and support the sustainable growth of the MSME's revenue.